The involvement of hippocampal CA3 TRP channels in anxiety and avoidance memory consolidation in rats tested in elevated plus maze - Zarrabian, Shahram; Nasehi, Mohammad; Zarrindast, Mohammad-Reza (Archives of Advances in Biosciences, 2016)
In the current study, we assessed the role of transient receptor potential (TRP) channels on avoidance memory and anxiety states in CA3 area of the hippocampus. We explored the anxiety and avoidance memory states using test-retest protocol in the elevated plus maze to understand whether TRP channels can affect the above mentioned states in CA3 area. To investigate the consolidation phase of memory, the drugs were injected into the CA3 region before the test. Our data showed that the application of SKF-96365 did not alter anxiety-like behaviors but induced avoidance memory impairment. It was revealed that CA3 TRP channels could affect the avoidance memory consolidation and their role must be considered in future research.